Method for preparing high-performance composite hard carbon by utilizing biomass waste, product prepared by method and application of product
By using biomass waste to prepare composite hard carbon materials, combined with the synergistic effect of tin source and NaCl template agent, the problem of unstable structure of the negative electrode material of sodium ion battery is solved, efficient sodium ion embedding and deintercalation is achieved, and the cycle life and rate performance of the battery is improved.
Patent Information
- Application Number
- CN202411775843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
AI Technical Summary
The structure of the existing sodium ion battery anode material is unstable during the charging and discharging process, resulting in a short battery cycle life and low charging and discharging efficiency.
Biomass waste is used to prepare high-performance composite hard carbon. Through the steps of oxygen-free pre-calcination, ball milling and high-temperature calcination, combined with the synergistic effect of the tin source and NaCl template agent, a composite hard carbon material with a porous structure and high specific capacity is formed.
It improves the reversible capacity and cycle stability of composite hard carbon materials, enhances the rate performance of the battery and the interface stability of the electrolyte, and extends the cycle life of the battery.
Smart Images

Figure CN119706786A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a method for preparing high-performance composite hard carbon using biomass waste, and products prepared therefrom and applications thereof. Background Art
[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, both of which store and release energy through the movement of ions between the positive and negative electrodes. In sodium-ion batteries, sodium ions are released from the positive electrode during charging, move to the negative electrode through the electrolyte and embed, and move in the opposite direction during discharge. For sodium-ion batteries, the negative electrode material is crucial to battery performance. It needs to have good conductivity, chemical stability and high specific capacity to ensure the rapid embedding and de-embedding of sodium ions, thereby improving the battery's charge and discharge efficiency and cycle life.
[0003] Compared with graphite, hard carbon has a larger interlayer spacing, which can adapt to the larger radius of sodium ions (0.102nm), while the interlayer spacing of graphite (0.335nm) limits the intercalation reaction of sodium ions. In addition, hard carbon has the advantages of high sodium storage capacity, good conductivity, low platform potential, small volume change during charge and discharge, and is not easy to pulverize, as well as environmental friendliness and low cost. These characteristics make hard carbon an ideal choice for negative electrode materials of sodium ion batteries.
[0004] Based on the above reasons, this application is filed. Summary of the invention
[0005] Based on the above reasons, in response to the problems or defects existing in the prior art, the purpose of the present invention is to provide a method for preparing high-performance composite hard carbon using biomass waste and the products and applications prepared therefrom, so as to solve or at least partially solve the above-mentioned technical defects existing in the prior art.
[0006] In order to achieve the above first object of the present invention, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing high-performance composite hard carbon using biomass waste, the method specifically comprising the following steps:
[0008] (1) crushing biomass waste to a size not exceeding 100 microns to obtain a dust-like material;
[0009] (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized material;
[0010] (3) The pre-carbonized material of step (2) is mixed with a tin source and a template according to a ratio, and then ball-milled. The ball-milled mixture is calcined at 1000-1400° C. for 3-4 hours. After calcination, it is cooled to room temperature. The calcined product is washed, dried, and crushed in turn to obtain the high-performance composite hard carbon.
[0011] Furthermore, in some embodiments, the biomass waste in step (1) can be one or more of coconut shells, bamboo, hard fruit shells, straw, grass leaves, etc. These biomass wastes are abundant in source and have high carbon yield.
[0012] Specifically, in the above technical solution, the purpose of the oxygen-free pre-calcination in step (2) is to discharge the tar in the hard carbon raw material to obtain a pre-carbonized material.
[0013] Furthermore, in the above technical solution, the time for the oxygen-free pre-calcination treatment in step (2) is 3-5 hours, preferably 4 hours.
[0014] Furthermore, in the above technical solution, during the anaerobic pre-calcination treatment in step (2), a protective gas may be introduced into the reaction system to accelerate the discharge of tar by purging with the protective gas.
[0015] Furthermore, in the above technical solution, the flow rate of the protective gas is 1-5 ml / s.
[0016] Furthermore, in the above technical solution, the protective gas is argon.
[0017] Furthermore, in the above technical solution, the mass ratio of the pre-carbonized material to the tin source and the template in step (3) is 100:(1.8-2.5):(4.5-5.5).
[0018] Furthermore, in some embodiments, the mass ratio of the pre-carbonized material to the tin source and the template is 100:2.03:5.2.
[0019] Furthermore, in some embodiments, the tin source in step (3) is any one of tin oxides such as tin dioxide and tin trioxide.
[0020] Furthermore, in some embodiments, the template in step (3) is NaCl.
[0021] The second object of the present invention is to provide a high-performance composite hard carbon prepared by the method described above.
[0022] The third object of the present invention is to provide the application of the high-performance composite hard carbon prepared by the above method in sodium ion batteries.
[0023] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the negative electrode is the high-performance composite hard carbon prepared by the above-mentioned method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The tin source used in the present invention provides doped Sn atoms for the preparation of high-performance composite hard carbon, which not only participates in the Faraday reaction of sodium ions, but also generates additional active sites without being removed or embedded with sodium ions, thereby improving the reversible capacity of the product. x -C (x = 1-4) helps to maintain the structural stability of the material during the charge and discharge process, reduce structural damage caused by volume expansion and contraction, improve electrolyte interface stability, and provide better rate performance.
[0026] (2) The synergistic effect of the use of the NaCl template agent used in the present invention and the Sn element provided by the tin source can further improve the electrochemical performance of the composite hard carbon material, improve the specific capacity and cycle stability. At the same time, during the high-temperature carbonization process, NaCl will decompose, leaving pores, thereby forming a porous structure. This porous structure is conducive to increasing the specific surface area of the material and increasing the adsorption and transmission channels of sodium ions.
[0027] (3) In the conventional process, the modification stage is generally at the back end, but the present invention performs the modification before calcination at the front end, which can greatly shorten the process flow.
[0028] (4) The present invention adopts a firing process with different temperatures, and different firing temperatures of the material tested will have different degrees of influence on the formation of the composite material.
[0029] (5) The composite hard carbon material manufactured using the method of the present invention can significantly improve the gram capacity, and the optimal temperature is explored. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a scanning electron microscope (SEM) image of the composite hard carbon material prepared in Example 1 of the present invention;
[0032] Figure 2This is a scanning electron microscope (SEM) image of the composite hard carbon material prepared in Example 4 of the present invention;
[0033] Figure 3 This is a comparison chart of the first charge and discharge cycle of button batteries prepared using Example 1 and Example 2 of the present invention as negative electrode active materials. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0035] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.
[0036] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0037] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0038] Example 1
[0039] A method for preparing high-performance composite hard carbon using biomass waste in this embodiment specifically comprises the following steps:
[0040] (1) Crushing: crushing the coconut shell raw material to particles not exceeding 100 microns;
[0041] (2) Anaerobic pre-calcination: The crushed raw material is sent to a box-type furnace in an argon atmosphere for pre-carbonization. The material is heated from room temperature, and the temperature is increased by 0.5 degrees Celsius per minute to 550 degrees Celsius for 3 hours. The temperature is then decreased by 0.5 degrees Celsius per hour to 25 degrees Celsius to obtain a pre-carbonized material.
[0042] (3) Mixed crystals: 100 g of the pre-carbonized material, 2.03 g of tin dioxide and 5.2 g of sodium chloride were mixed thoroughly;
[0043] (4) Dry ball milling: 3 mm and 5 mm zirconium beads are added into the ball mill of the ball mill in a mass ratio of 2:1, and then the mixed raw materials obtained in step (3) are added, and ball milling is started. The speed of the ball mill is controlled to be 60%-90%. After six hours of ball milling, the mixture is allowed to stand and the zirconium beads are removed by screening; wherein: the total volume of the zirconium beads, the volume occupied by the mixed raw materials, and the volume ratio of the remaining space are 3.5:3.5:3; wherein: the remaining space refers to the spatial volume of the ball mill after deducting the volume of the zirconium beads and the volume occupied by the mixed raw materials from the total volume of the ball mill.
[0044] (5) High-temperature calcination: The ball-milled raw material obtained after standing and sieving to remove the zirconium beads in step (4) is placed in an orbital furnace and heated in a stepwise manner at a heating rate of 2 degrees Celsius per minute until it reaches 1400 degrees Celsius. The temperature is then kept at this temperature for three hours. After the calcination is completed, the temperature is cooled to room temperature at a rate of 2 degrees Celsius per minute.
[0045] (6) The product obtained by cooling in step (5) is poured into distilled water for washing, and the solid-liquid ratio is controlled to be 1 mg:3-5 ml; after washing twice, it is placed in a forced air drying oven for drying, and the drying temperature is controlled to be 60-90 degrees Celsius, and the drying time is 4-6 hours.
[0046] (7) The dried material from step (4) is placed in an air flow mill for crushing and screening, with the air flow pressure controlled at 0.7 MPa, the feed rate at 2 kg / h, and the gas flow rate at 6 m2 / min, to obtain high-performance composite hard carbon with a size of 10 μm.
[0047] Example 2
[0048] The present embodiment provides a method for preparing high-performance composite hard carbon using biomass waste. The method is basically the same as that of Example 1, with the only difference being that the amount of tin dioxide used in step (2) of the present embodiment is 1.8 g.
[0049] Example 3
[0050] The present embodiment provides a method for preparing high-performance composite hard carbon using biomass waste. The method is basically the same as that of Example 1, with the only difference being that the amount of tin dioxide used in step (2) of the present embodiment is 2.5 g.
[0051] Example 4
[0052] The present embodiment provides a method for preparing high-performance composite hard carbon using biomass waste. The method is basically the same as that of the first embodiment, with the only difference being that the temperature of high-temperature calcination in step (5) of the present embodiment is 1000 degrees Celsius.
[0053] Example 5
[0054] The present embodiment provides a method for preparing high-performance composite hard carbon using biomass waste. The method is basically the same as that of the first embodiment, with the only difference being that the temperature of high-temperature calcination in step (5) of the present embodiment is 1200 degrees Celsius.
[0055] Example 6
[0056] The present embodiment provides a method for preparing high-performance composite hard carbon using biomass waste. The method is basically the same as that of the first embodiment, with the only difference being that the temperature of high-temperature calcination in step (5) of the present embodiment is 1600 degrees Celsius.
[0057] Structural and performance testing:
[0058] Figure 1 This is a scanning electron microscope (SEM) image of the composite hard carbon material prepared in Example 1 of the present invention. Figure 1 It can be seen that the surface of the obtained composite hard carbon material is rough and has irregular protrusions, which shows that tin dioxide can effectively affect the structure of hard carbon at 1400 degrees Celsius, making its surface rougher, and it can also show that the Sn element is doped at 1400 degrees Celsius.
[0059] Figure 2 This is a scanning electron microscope (SEM) image of the composite hard carbon material prepared in Example 4 of the present invention. Figure 2 It can be seen that the surface of the prepared composite hard carbon material is relatively smooth, the distance between particles is large, and the surface structure of the hard carbon material is not well affected. This indicates that at 1000 degrees Celsius, the doping rate of the Sn element is relatively low and has little impact on the surface of the hard carbon material.
[0060] The composite hard carbon materials prepared in the above Examples 1-6 were respectively used as negative electrode active materials to assemble button batteries, and the specific method was as follows:
[0061] The negative electrode plate is composed of a composite hard carbon material, Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, wherein the mass ratio of the composite hard carbon material, Super P, SBR and CMC is 90:2:4:4. The composite hard carbon material powder and Super P conductive carbon are ground in proportion for 20 minutes and mixed evenly. The mixed composite hard carbon material and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), placed on a micro ball mill and stirred for 15 minutes to obtain a uniform slurry, and the slurry is evenly coated on aluminum foil (the coating amount is 110.23g / cm 2 ), vacuum dried in an oven at 120°C for 5 hours, and punched out negative electrode sheets with a diameter of 12 mm using a gun press, which were weighed and set aside for use.
[0062] A sodium ion battery half-cell is formed by using a sodium sheet as the positive electrode, the negative electrode is the negative electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 180 mA / g, the test voltage range is 0.05 V-2 V, and the button battery is subjected to a charge and discharge cycle test.
[0063] Figure 3 The first charge and discharge cycle comparison diagram of the button battery prepared with Example 1 and Example 2 of the present invention as the negative electrode active material. Table 1 summarizes the first discharge gram capacity of the battery made of materials under different proportions and different temperatures. It can be seen from the summary table that Example 1 is the most advantageous preparation condition for the material.
[0064] Table 1 Comparison of electrochemical performance of button cells obtained using composite hard carbon materials prepared in Examples 1-6
[0065]
Claims
1. A method for preparing high-performance composite hard carbon using biomass waste, characterized in that: The method specifically comprises the following steps: (1) crushing biomass waste to a size not exceeding 100 microns to obtain a dust-like material; (2) pre-calcining the dusty material in step (1) at 500-600° C. in the absence of oxygen, and cooling to room temperature after the pre-calcination to obtain a pre-carbonized material; (3) The pre-carbonized material of step (2) is mixed with a tin source and a template according to a ratio, and then ball-milled. The ball-milled mixture is calcined at 1000-1400° C. for 3-4 hours. After calcination, it is cooled to room temperature. The calcined product is washed, dried, and crushed in turn to obtain the high-performance composite hard carbon.
2. The method according to claim 1, characterized in that: The biomass waste in step (1) is one or more of coconut shells, bamboo, hard fruit shells, straw, and grass leaves.
3. The method according to claim 1, characterized in that: The time of the oxygen-free pre-calcination treatment in step (2) is 3-5 hours.
4. The method according to claim 1, characterized in that: In step (3), the mass ratio of the pre-carbonized material to the sulfur source and the template agent is 100:(1.8-2.5):(4.5-5.5).
5. The method according to claim 4, characterized in that: The mass ratio of the pre-carbonized material to the sulfur source and the template agent is 100:2.03:5.
2.
6. The method according to claim 1, characterized in that: The sulfur source in step (3) is sodium sulfite or sodium thiosulfate.
7. The method according to claim 1, characterized in that: The template in step (3) is NaCl.
8. A high performance composite hard carbon material prepared by the method according to any one of claims 1 to 7.
9. Application of the high-performance composite hard carbon material prepared by the method according to any one of claims 1 to 7 in sodium ion batteries.
10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a high-performance composite hard carbon material prepared by the method described in any one of claims 1-7.